Factors to affect improvement in cyber officer performance. (13th June 2016) - Helkala, Kirsi; Knox, Benjamin; Jøsok, Øyvind; Knox, Silje; Lund, Mass
Abstract : Purpose: The purpose of this study is to investigate how motivation – gained by understanding the purpose of specific cyber-oriented tasks – coping strategies and level of physical conditioning can affect cognitive abilities amongst cyber officer cadets. Design/methodology/approach: Two cognitive tests (2014 and 2015) and coping strategy questionnaires (2015) were conducted during an annual military exercise involving increased levels of stress and hardship (physical and cognitive) over a sustained two-week period. Findings: Motivation – gained by task explanations – and the conscious use of the "control" strategy can have a positive effect on individual performance in cyber tasks. Research limitations/implications: The participants were all young adults with higher-than-average levels of physical fitness. From the outset, all participants were highly motivated and disciplined having entered cyber officer training after successfully completing a thorough selection process. Practical implications: The results of this study are to be better implemented to the activities at the military academy. Social implications: The closest civilian occupational equivalent is a computer network operations (CNO)-operator. The findings could be implemented into their daily work routines. Originality/value: Cognitive tests used in this study are based on recognized general cognitive tests. However, modifications were made to suit the cyber task context, making the test original. The cyber officer is a contemporary concept currently lacking research.